2021
DOI: 10.1021/acs.jpcc.1c05859
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review on the Physical Properties of Gallium-Based Liquid Metals and Selected Pathways for Their Alteration

Abstract: Gallium-based liquid metals have gained plenty of attention in the scientific community due to their extraordinary properties. The most intriguing properties of liquid metals are high surface tension, density anomaly, high electrical and thermal conductivity, phase transition, and their temperature and low viscosity in combination with their low toxicity. Though there are many reports of the physical properties of gallium-based liquid metals, some of these are highly scattered and inconsistent. Therefore, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 288 publications
(668 reference statements)
3
70
0
5
Order By: Relevance
“…As shown in Figure 2 b, the Ga–PU composite shows two melting temperatures in the DSC heating curve, and two crystallization temperatures in the DSC cooling curve. In the composite, the Ga microdroplets crystallize at a much lower temperature (–33.3 °C) during the cooling process, due to the supercooling and size effects [ 55 , 56 ], while melting is observed at 29.4 °C during the heating process. The other peak, at around −10.0 °C in the cooling curve, is attributed to the crystallization of PCL segments in the PU elastomer.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2 b, the Ga–PU composite shows two melting temperatures in the DSC heating curve, and two crystallization temperatures in the DSC cooling curve. In the composite, the Ga microdroplets crystallize at a much lower temperature (–33.3 °C) during the cooling process, due to the supercooling and size effects [ 55 , 56 ], while melting is observed at 29.4 °C during the heating process. The other peak, at around −10.0 °C in the cooling curve, is attributed to the crystallization of PCL segments in the PU elastomer.…”
Section: Resultsmentioning
confidence: 99%
“…Liquid metal was chosen as it features fluidity (ca. 2 mP s), rendering it nearly infinitely bendable and stretchable, and high electrical conductivity (~3.4 × 10 4 S/cm) [ 41 ]. Furthermore, it remains in its liquid state far below its melting temperature of 10.5 °C (Galinstan) due to supercooling, and freezing is typically observed at temperatures below −20 °C [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 mP s), rendering it nearly infinitely bendable and stretchable, and high electrical conductivity (~3.4 × 10 4 S/cm) [ 41 ]. Furthermore, it remains in its liquid state far below its melting temperature of 10.5 °C (Galinstan) due to supercooling, and freezing is typically observed at temperatures below −20 °C [ 41 ]. Therefore, both the liquid metal and the hydrogel are endowed with moldability at subzero temperatures, and should be an interesting approach for hydrogel soft electronics.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the fatigue resistance of LCE materials, we have tried to incorporate many reinforcing materials such as gold nanoparticles, carbon nanotubes, and carbon fibers into LCE matrices for introducing extra physical associations to strengthen the chain networks of LCEs [21], which however failed in substantially enhancing the fatigue resistance of LCEs. Recently, Ware, Majidi and other scientists described a liquid metal (LM)-doped LCE composite, which could realize electricdriven actuation based on the Joule-heating effect [26][27][28][29][30], and found that the introduction of LM [31][32][33] fillers into LCE materials could bring many advantages including fluidic nature, negligible toxicity, and flexibility. However, in order to achieve high electrical conductivity for electrothermal conversion, large quantity (~50 vol%) of LM microdroplet (~200 to 500 μm) fillers were incorporated into LCE matrices which did not markedly boost the mechanical performances of the corresponding composites [26].…”
Section: Introductionmentioning
confidence: 99%